Naturally Competent Acinetobacter baumannii Clinical Isolate as a Convenient Model for Genetic Studies - Ramirez, Maria Soledad (2010)
Acinetobacter baumannii A118 was isolated from a patient´s blood culture. It is susceptible to several antibiotics, is naturally competent, and supports replication and stable maintenance of four plasmid replicons. A. baumannii A118 took up a fluorophore-labeled oligonucleotide analog. These characteristics make this isolate a convenient model for genetic studies.